Primary Umbilical Endometriosis in an Adolescent Girl: Unsuspected Pathology - Nellihela, Leel; Al-Adnani, Mudher; Kufeji, Dorothy (European Journal of Pediatric Surgery Reports, 2020)
Endometriosis affects 7 to 10% of women of reproductive age. Primary umbilical endometriosis (PUE) is even rarer with unclear pathogenesis. We report a case of PUE possibly the youngest patient reported in the literature.A 16-year-old girl of African origin presented with painful umbilical lump for 2 to 3 months duration with background history of precocious puberty, cyclical vomiting, and menorrhagia. Clinical examination showed dark-colored, tender, irreducible umbilical lump. A provisional diagnosis of incarcerated umbilical hernia was made. Abdominal X-ray showed no features of intestinal obstruction. Ultrasound scan of the abdomen showed lump containing heterogeneous echogenic material measuring 2.0 × 1.5cm within the umbilicus with no visible bowel loops or peristalsis. This was reported as consistent with an umbilical hernia with narrow neck possibly containing mesentery or intra-abdominal fat. The patient underwent urgent exploration of umbilicus under general anesthetic. At operation, a dark-colored, firm mass was excised and sent for histology. The underlying fascia and peritoneum were repaired.Histological examination confirmed the excised tissue was endometriosis. Follow-up continues in the endometriosis clinic.Umbilical endometriosis should be considered in differential diagnoses of painful umbilical lesion in adolescent girls and women of reproductive age. Complete excision and histology are highly recommended for obtaining a definitive diagnosis, to exclude malignancy and to prevent recurrence.
Keywords: endometriosis; umbilical; primary; adolescent